Influence of Age on Serum Protein Capillary Electrophoretic Pattern in Clinically Healthy Calves with Special Emphasis on Serum Globulins - M. Elkhair, Nawal; Hartmann, H. (Journal of Veterinary Medicine and Animal Production, 2022)
The objective of this study was to characterise serum protein capillary electrophoretic pattern in relation to the age in calves. Thirty two German Black-coloured and crossbred calves (age: 4-104 days) were used. Venous blood samples were collected from the jugular vein and were used for the determination of serum protein; by capillary electrophoresis technique. The age of the calves correlated positively (P<0.01) with serum albumin concentration and albumin/globulin ratio. The youngest calves in the first week of life showed significantly (P<0.05) lower mean serum albumin compared to the older calves of 2-3 months. The concentrations of α1, β- and γ- globulin were not affected significantly by age. The young calves in the 2nd week of life showed significantly (P<0.01) higher mean value for α2 globulin concentration compared to the old calves (1-3 months). Albumin/globulin ratio showed significantly (P<0.01) higher value in the young calves in the 2nd week of life compared to the old calves in the age of 1-2 months. These values were compared to those reported by other investigators in calves, adult cattle and other animals. The results indicate that the serum electrophoresis pattern of the calves is influenced by age